Pengaruh Etos Kerja Guru Pendidikan Agama Islam terhadap Motivasi Belajar Peserta Didik - Nur Zaini; Suci Isnainia Devi Ningrum (Fakultas Agama Islam Universitas Billfath, 2022)
Indicators of personality competence, teachers must have a high work ethos and responsibility in carrying out their duties. The teacher's high work ethos will indirectly have an impact on students' learning motivation. This research is quantitative correlation research. The data collection method used a questionnaire method which was distributed to 39 respondents and the documentation method. The data analysis method used the percentage formula and product moment correlation with results: 1) The work ethic of the PAI teacher at SMA Ma'arif NU Nurul Huda Pucuk in school year of 2020/2021 was in the high category with a total percentage gain of 67.64%. 2) The learning motivation of class XI students of SMA Ma'arif NU Nurul Huda Pucuk in school year of the 2020/2021 was in the high category with a total percentage gain of 64.7%. 3) PAI Teacher's Work Ethic on Learning Motivation of Class XI Students of SMA Ma'arif NU Nurul Huda Pucuk for the 2020/2021 Academic Year. Based on the calculation of the Product Moment Correlation which has been adjusted to the rTable level of 5%. It can be seen that rCount (0.349) > rTable (0.316), which means that the alternative hypothesis (Ha) is accepted, namely that there was an influence of PAI teacher work ethos on the learning motivation of class XI students in school year 2020/2021 with a low interpretation because it is in the coefficient interval 0.20 – 0.399.